2015
DOI: 10.1016/j.porgcoat.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Structure-scratch properties relationships of acrylate photo-polymerizable protective coatings for thermoplastic substrates

Abstract: International audienceThe relationships between the composition and the scratch resistance of clear photo-polymerized protective coatings for thermoplastic substrates were studied in relation with their thermomechanical properties. For this purpose, dynamic mechanical analyses of free-standing films were compared to micro-scratch tests of thick or thin coatings deposited on polycarbonate. In these experiments, the depth indented by the tip, the elastic recovery of the material, the residual depth of the scratc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…As for the critical load [Fig. (d)], the improvement is remarkable with respect to a classical petro‐based formulation that showed a 1.9 N critical load under the same test conditions, that is, an increase ranging from ∼60% for Bio 12 to ∼175% for Bio 13. All the studied coatings are thus effective in terms of protection against scratches.…”
Section: Resultsmentioning
confidence: 92%
“…As for the critical load [Fig. (d)], the improvement is remarkable with respect to a classical petro‐based formulation that showed a 1.9 N critical load under the same test conditions, that is, an increase ranging from ∼60% for Bio 12 to ∼175% for Bio 13. All the studied coatings are thus effective in terms of protection against scratches.…”
Section: Resultsmentioning
confidence: 92%
“…The purpose of an HC in general is to increase the hardness and scratch resistance via a hard coat layer over the substrate surface. An HC can involve an organic oxide, epoxy resin, polyurethane silicone, or polyacrylate, showing plastic deformation on scratches [64][65][66]. Xu et al reported a study wherein UV-cured acrylates were used as a hard coating for a PMMA/PC substrate, and the properties were tested using the pencil hardness test and progressive normal scratch test [67].…”
Section: Overview Of Coatings For Pc Substratesmentioning
confidence: 99%